NEW AGE DATA ON GOLD-QUARTZ MINERALIZATION IN THE VERKHNYAYA INDIGIRKA AREA, YAKUTIA - Akimov G.Yu. (My University, 2004)
The gold-quartz deposits of the Verkhnyaya Indigirka area of Yakutia formed during Mesozoic tectonogenesis, which was related to the collision between the Kolyma-Omolon composite terrain and North Asian craton at the end of the Jurassic and the beginning of the Neocomian. These deposits are located in Upper Permian-Upper Triassic terrigenous rocks of the Verkhoyansk Complex far away from granitoid massifs. Since the gold-quartz veins have no geological relationship with granitoids and were not dated, the position of this mineralization in the evolution of the Mesozoic is uncertain. Some geologists suggest that gold-quartz mineralization has a pregranite age. Our geological, petrographical, and geochronological investigations established that the gold-quartz mineralization of this region is related to the Early Neocomian adamellite-granite complex, the emplacement of which caused regional zonal metamorphism.